DETERMINATION OF QUANTITATIVE LEVEL OF PROCALCITONIN AND ESTIMATION OF ITS DYNAMICS IN PATIENT WITH SYSTEMIC TYPE OF JUVENILE RHEUMATOID ARTHRITIS - A.M. Chomakhidze; E.I. Alexeeva; S.I. Valieva; T.M. Bzarova; R.V. Denisova ("Paediatrician" Publishers LLC, 2008)
Questions of differential diagnosis in conditions of developed systemic inflammatory reaction in patients with systemic type of juvenile rheumatoid arthritis (JRA) are one of difficult problems in children's rheumatology. Clinical signs, similar to sepsis, accompanied by development of symptoms of inflammatory reaction may be observed in patients with systemic type of JRA at the time of exacerbation of main disease, or due to development of bacterial complications and medicinal reactions, or it may be the consequence of combination of these reasons. Presented case report allows making a conclusion that using of procalcitonin test, especially quantitative one, in usual practice of rheuma tologist permits to carry out a differential diagnosis between infectious and autoimmune reasons of developed systemic inflammatory reaction, to start an etiotropiс and/or pathogenetic treatment at the proper time, to estimate the severity of pathological process and activity of therapy in first days from its onset, and to determine an optimal duration of treatment. Key words: juvenile rheumatoid arthritis, procalcitonine test, differential diagnosis.